Dynamic histogram equalization, PCA & MAX-DCT based multi-focus image fusion (International Journal of Engineering and Computer Science, 2014)
The idea of image fusion in multi-focus cameras to combine data from various images of the similar landscape in order to bring the multi focused image. Discrete cosine transform is an image fusion method which is extra appropriate and acceptable in real-time systems using discrete cosine transform based standards of motionless image or video. This review paper shows an arranged approach for fusion of multi-focus images which is based on variance calculated in discrete cosine transform domain. In this paper a new technique is proposed which will combine the PCA, Max-DCT and dynamic histogram equalization to raise the outcome. The proposed algorithm is calculated and implemented in MATLAB using image processing toolbox. The experiments have shown that the proposed algorithm outperforms over the available techniques